The Eµ-hnRNP K Murine Model of Lymphoma: Novel Insights into the Role of hnRNP K in B-Cell Malignancies - Malaney, Prerna; Velasco-Estevez, María; Aguilar-Garrido, Pedro; Aitken, Marisa J. L.; Chan, Lauren E.; Zhang, Xiaorui; Post, Sean M.; Gallardo, Miguel (Frontiers in Immunology, 2021)
B-cell lymphomas are one of the most biologically and molecularly heterogeneous group of malignancies. The inherent complexity of this cancer subtype necessitates the development of appropriate animal model systems to characterize the disease with the ultimate objective of identifying effective therapies. In this article, we discuss a new driver of B-cell lymphomas – hnRNP K (heterogenous nuclear ribonucleoprotein K) – an RNA-binding protein. We introduce the Eµ-Hnrnpk mouse model, a murine model characterized by hnRNP K overexpression in B-cells, which develops B-cell lymphomas with high penetrance. Molecular analysis of the disease developed in this model reveals an upregulation of the c-Myc oncogene via post-transcriptional and translational mechanisms underscoring the impact of non-genomic MYC activation in B-cell lymphomas. Finally, the transplantability of the disease developed in Eµ-Hnrnpk mice make it a valuable pre-clinical platform for the assessment of novel therapeutics.